2021
DOI: 10.3390/cells10113258
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endocytosis Proteins in Gefitinib-Mediated EGFR Internalisation in Glioma Cells

Abstract: EGFR (epidermal growth factor receptor), a member of the ErbB tyrosine kinase receptor family, is a clinical therapeutic target in numerous solid tumours. EGFR overexpression in glioblastoma (GBM) drives cell invasion and tumour progression. However, clinical trials were disappointing, and a molecular basis to explain these poor results is still missing. EGFR endocytosis and membrane trafficking, which tightly regulate EGFR oncosignaling, are often dysregulated in glioma. In a previous work, we showed that EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Dysregulated endocytosis and membrane trafficking of RTKs mediated by endosomes maintains glioblastoma malignancy ( 46 ). SNX family proteins have been implicated in endosomal sorting and endosomal homeostatic maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated endocytosis and membrane trafficking of RTKs mediated by endosomes maintains glioblastoma malignancy ( 46 ). SNX family proteins have been implicated in endosomal sorting and endosomal homeostatic maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…endosomes maintains glioblastoma malignancy (46). SNX family proteins have been implicated in endosomal sorting and endosomal homeostasis maintenance.…”
Section: Dysregulated Endocytosis and Membrane Trafficking Of Recepto...mentioning
confidence: 99%
“…A number of patients can benefit from TKI treatment, while others will still suffer from recurrence ( 34 ). It has been reported that internalization of EGFR mediated by endocytosis is one of the direct reasons for TKI treatment failure ( 35 ). In addition, tumors can also become drug resistant through a bypass activation mechanism, leading to poor prognosis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gefitinib (ZD1839; Iressa), a small molecular weight EGFR kinase inhibitor, has been given approval for the treatment of locally advanced and metastatic non-small cell lung cancer, or NSCLC. [47] A humanised monoclonal antibody called cetuximab (C225; Erbitux interacts the both EGFR and EGFRvIII extracellular domains. It has been authorised for the treatment of head and neck squamous cell carcinoma that has spread or recurred after previous chemotherapy.…”
Section: Molecular Markers Associated With Glioma: Mgmtmentioning
confidence: 99%